Content, Identity Building and National Curricula - Läänemets, Urve; Kalamees-Ruubel, Katrin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Theoretical research on curriculum development and implementation has been a rich and highly diverse field of study in the second half of the 20th century and the first decade of the 21st , including Estonia, but the selection of educational content for general comprehensive schools has not been a priority. Some reasons for difficulties with regard to making informed decisions about the selection of the content can be found in the constantly growing amount of new knowledge, global developments and in cultural differences within and between societies. The acknowledged political goal for organising general education for the majority of countries in Europe (and all over the world) has been the development of a cohesive and sustainable society, which can be built on acknowledged and accepted common values. Research on the potential of school subjects can contribute to that and open new vistas for development of national curricula.